Sistema de Notificaciones de Incidencias Escolares a través de Mensajería Móvil para los Estudiantes de la Escuela de Educación Básica Juan Antonio Montalván Cornejo de la Ciudad de Vinces - Rosado Anzules, José Manuel (2018)
Education is the fundamental axis for the advancement of a country, mainly primary education, which in addition to teaching reading to write is responsible for promoting ethical, moral and civic values; a very important issue for the development of children. However, it should be remembered that not only does the school have the role of training children, but it is a shared responsibility between teachers and parents. However, in the School of Basic Education Juan Antonio Montalván Cornejo of the City of Vinces, there are drawbacks in communication between teachers and parents, which causes ignorance of the academic status of their children, showing a certain degree of irresponsibility on the part of the students. parents, which is reflected in unfulfilled tasks by children. Technology, currently growing by leaps and bounds, this is a very good reason to use it with the aim of creating computer solutions that automate processes that solve the problems that are present in this educational institution. The present work describes the development of a system of notifications through mobile messaging in the School of Basic Education, to keep informed the parents of the events that happen in this institution, besides notifying the academic report of the students, as well as their tasks.